Severe acute pancreatitis secondary to the use of immune checkpoint inhibitors - Arango Molano, Lázaro (2026)
ICI-induced pancreatic injury is a rare subtype of immune-related adverse events. Although it is a relatively rare event and most patients who present it are asymptomatic, a subgroup of patients may present clinical and radiological manifestations typical of severe acute pancreatitis, with long-term sequelae of endo- and exocrine pancreatic function. Advanced age, the combination of ICIs, preexisting autoimmune diseases, and tumor type have been described as risk factors for developing this pathology. We report the case of a patient with metastatic renal cancer, a history of partial pancreatectomy, treated with checkpoint inhibitors, who developed severe acute pancreatitis with the formation of walled-off pancreatic necrosis after the third application. Other etiologies were ruled out; multidisciplinary management and endoscopic management with endosonographic drainage with apposition stent were provided, with a successful outcome and clinical recovery of the patient.